Aerobic exercise attenuates insulin resistance via restoring branched chain amino acids homeostasis in obese mice - Wei Cao; Wei Cao; Yajin Liu; Hao Wei; Yunfeng Dong; Haipeng Sun; Haipeng Sun; Xuejiao Zhang; Xuejiao Zhang; Junqiang Qiu; Junqiang Qiu (Frontiers in Nutrition)
IntroductionEmerging evidences suggests that the disrupted branched-chain amino acids (BCAAs) homeostasis and elevated BCAAs promote obesity-related insulin resistance (IR). Exercise improves insulin sensitivity. However, whether BCAAs plays a role in the exercise-attenuated IR remains to be fully investigated.MethodsIn this study, male C57BL/6J mice were induced to become diet-induced obese (DIO) and served as subjects. The initial investigation focused on the impact of exercise on IR and BCAAs. The DIO mice were randomly assigned to either a sedentary group (CON, n = 16) or an exercise group (EX, n = 16). The EX group underwent a 12-week aerobic exercise regimen on a treadmill. After 12-week, plasma BCAAs and branched-chain keto acids (BCKAs) were measured by liquid chromatography-mass spectrometry, glucose tolerance test (GTT) and insulin tolerance test (ITT) were performed, and the expression and phosphorylation of BCAAs catabolic proteins, as well as AKT T308 in gastrocnemius muscle and liver tissues, were evaluated using western blotting. Subsequently, the study explored the role of BCAAs in enhancing IR through exercise. Mice were randomly allocated into 4 groups: sedentary group (CON, n = 8), sedentary with BCAAs supplementation group (CON+BCAA, n = 8), exercise group (EX, n = 16), and exercise with BCAAs supplementation group (EX+BCAA, n = 16). The exercise protocol was as above. Mice in the BCAAs supplemented groups received drinking water containing 2% BCAAs. After 12-week, plasma BCAAs and BCKAs were measured, GTT and ITT tests were performed, and the phosphorylation of AKT T308, as well as p70S6K T389 in gastrocnemius muscle and liver, were compared between the EX group and the EX+BCAA group. Additionally, the phosphorylation of AMPKα T172 in both tissues was measured across all four groups.Results12-week aerobic exercise improved insulin sensitivity in DIO mice while inducing BCAAs catabolic protein expression in skeletal muscle and liver, and reducing the plasma BCAAs level. Importantly, BCAAs supplementation elevated the plasma level of BCAAs and counteracted the exercise-attenuated IR. In skeletal muscle and liver tissues, BCAAs supplementation impaired the exercise-improved insulin signaling without enhancing mammalian target of rapamycin activity. AMPK activity was enhanced by aerobic exercise, which was abolished by BCAAs supplementation.ConclusionAerobic exercise attenuated insulin resistance via restoring BCAAs homeostasis and AMPK activity. The impacts of BCAAs intake on the metabolic effects of exercise sheds light on the combined exercise and nutrition intervention strategy for diabetes management.